Toward a Race Pedagogy for Black Faculty. (August 2014) - Closson, Rosemary B.; Bowman, Lorenzo; Merriweather, Lisa R.
Educators are consciously or unconsciously guided by pedagogy and make critical decisions about praxis—content, strategy, structure—based on their pedagogical beliefs. The intentional use of pedagogy is often advanced as a key to being an effective educator. A wealth of literature is directed toward helping White educators develop a race pedagogy, but the authors argue Black educators who teach courses about race face unique challenges and should develop a pedagogical stance consistent with that reality. In this article, the authors analyze different strategies as evidence that Black faculty struggle to develop a pedagogy for teaching race. The authors argue for a purposeful, engaged pedagogy, and contextually informed pedagogy that sets conditions wherein both the educator and student take risks in exposing their authentic self and positionality.